Estimation of starch content in cassava based on coefficient of reflection measurement - Odedeyi, Temitope; Rabbi, Ismail; Poole, Clive; Darwazeh, Izzat (Frontiers in Food Science and Technology, 2022)
This technology report validates the application of radio frequency (RF) coefficient of reflection (Γ) measurement as a viable and accurate means to estimate the starch content of fresh cassava roots. A clear relationship between cassava dry matter as an indicator of starch content and the measured return loss is experimentally verified both from the measurement of cassava flour in water at different concentrations and by direct probing of cassava root samples at a specific frequency of 30 MHz. A prototype test instrument is then designed with goals of portability, low cost, and simplicity of use. The test instrument displays estimated starch content in 5 categories, from "low" to "high", using an array of 5 LEDs. The performance of the test instrument is experimentally verified in the field, and a reliable correlation between cassava dry matter content and LED indication is demonstrated.